Andrea Palladio and the Genesis of a Rotunda in the Residential Construction of French Classicism - Klimenko, Julia G. (Actual Problems of Theory and History of Art, 2016)
The article is focused on the problem of infiltration of architectural ideas of Italian Renaissance in the building practices of French classicism. It deals with the phenomenon of a rotunda in the residential architecture of Europe in modern times. The path of its evolution is traced from the “pièce à italienne” to “salon à la française”. The domed rotunda was borrowed from Italian temple architecture and won dwellings in France of classical and neoclassical periods: from palaces and townhouses to pavilions. The article presents numerous examples: buildings, fulfilled and unfulfilled projects, the training projects of the Royal Academy of Architecture and School of Bridges and Roads. The architectural module with the domed rotunda became widely spread in architecture around the world.
Keywords: Renaissance; Andrea Mantegna; French classicism; rotunda; French round salon; annular barrel vault with central support